Rapid and reliable genotyping of the C181T polymorphism in the bradykinin B2 receptor Gene - Weiß, Johanna; Hesse, Christiane; Haefeli, Walter E. (Clinical chemistry and laboratory medicine, 2003)
Bradykinin is not only a mediator of pain and inflammation but also a potent vasodilator and is likely to contribute to the cardioprotective effects of angiotensin-converting enzyme inhibitors. The B 2 receptor (B 2 -R) mediating most of the inflammatory and cardiovascular effects of bradykinin represents a candidate gene likely involved in the complex genetic causes of common chronic disorders such as hypertension. The C 181 T polymorphism of the B 2 -R gene influences the potency of bradykinin and there is evidence of a possible role of this polymorphism in the development of hypertension and end-stage renal disease. We developed and validated a new, rapid, and reliable method for the detection of the C 181 T polymorphism based on the hybridization probes format on the LightCycler™, which is superior to the conventional PCR-RFLP method commonly used to detect this polymorphism. It allows the solid evaluation of large patient populations with the best time.
Gesehen am 25.05.2021